2020
DOI: 10.5194/egusphere-egu2020-21893
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The RHOSSA campaign: Multi-resolution monitoring of the seasonal evolution of the structure and mechanical stability of an alpine snowpack

Abstract: <p>The necessity of characterizing snow through objective, physically-motivated parameters has led to new model formulations and new measurement techniques. Consequently, essential structural parameters such as density and specific surface area (for basic characterization) or mechanical parameters such as the critical crack length (for avalanche stability characterization) gradually replace the semi-empirical indices acquired from traditional stratigraphy. These advances come along with new deman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Both physically based models are driven with meteorological data from either automatic weather stations or numerical weather prediction models (e.g., Bellaire and Jamieson, 2013;Quéno et al, 2016) and provide microstructural (e.g., grain size) and macroscopic (e.g., density) properties for each snow layer. Validation campaigns have demonstrated a reasonably good agreement between modeled and observed snow stratigraphy (e.g., Durand et al, 1999;Lehning et al, 2001;Monti et al, 2009;Calonne et al, 2020) and, in particular, have confirmed the models' capability to reproduce critical snow layers such as surface hoar (Bellaire and Jamieson, 2013;Horton et al, 2014;Viallon-Galinier et al, 2020). From the basic model output, different mechanical properties can be calculated.…”
Section: Introductionmentioning
confidence: 71%
“…Both physically based models are driven with meteorological data from either automatic weather stations or numerical weather prediction models (e.g., Bellaire and Jamieson, 2013;Quéno et al, 2016) and provide microstructural (e.g., grain size) and macroscopic (e.g., density) properties for each snow layer. Validation campaigns have demonstrated a reasonably good agreement between modeled and observed snow stratigraphy (e.g., Durand et al, 1999;Lehning et al, 2001;Monti et al, 2009;Calonne et al, 2020) and, in particular, have confirmed the models' capability to reproduce critical snow layers such as surface hoar (Bellaire and Jamieson, 2013;Horton et al, 2014;Viallon-Galinier et al, 2020). From the basic model output, different mechanical properties can be calculated.…”
Section: Introductionmentioning
confidence: 71%
“…Proksch et al (2015), whileCalonne et al (2020) used 1 mm andKing et al (2020) 5 mm. However, the strength of the influence can be at least partially invalidated by the fact thatCalonne et al (2020) state that they tested for sensitivity of three different window sizes of 1, 2.5 and 5 mm and could not find a significant influence on the result -which is not quantified in the publication. At least choosing a fixed window for each parameterization -as we did with the 2.5 mm windowincreases the comparability.…”
mentioning
confidence: 99%
“…At least choosing a fixed window for each parameterization -as we did with the 2.5 mm windowincreases the comparability. Another limitation might be that theProksch et al (2015) calibration was made with a SMP version 2, while we,Calonne et al (2020) andKing et al (2020) use the newest SMP version 4.…”
mentioning
confidence: 99%
“…In winter 2017, the campaign to monitor the isotope signal in the snowpack took place from January to June (Figures 1a and 1b). In parallel to the isotope profile sampling campaign, an extensive measurement program to characterize the snow cover at the WFJ site took place (Calonne et al., 2020).…”
Section: Experimental and Modeling Methodsmentioning
confidence: 99%